Edukasi Program “SADARI” Pada Wanita Usia Subur Desa Sungai Adong Kuala Dua Kecamatan Sungai Raya - Lidia Hastuti; Tri Wahyuni; Annisa Rahmawati; Ridha Mardiani; Nora Gracesara; Selly K (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2021)
Current women's health problems should receive serious attention. In Indonesia, the highest mortality rate is experienced by women of productive age (15-49 years). Women are very susceptible to various diseases, including breast cancer which is the number 2 killer disease in the world. Breast cancer is a disease that can affect anyone, especially women. Breast cancer is the most common cancer in women. Currently, cancer is the second leading cause of death. Incidence and death rates continue to increase in developing countries because early detection and treatment facilities are inadequate. The output of this activity is to increase knowledge and change behavior for early detection of breast cancer through BSE in Sungai Adong Kuala Dua village. The target of the activity is housewives in Sungai Adong village. Activity method by providing education and simulation of BSE techniques. The results showed that there was an increase in the pre-test score of knowledge about breast cancer from the pres test score of 30 ± 8.2 to 88 ± 3.4 during the post test. While knowledge of BSE techniques, the pre test score of 20 ± 10.1 increased to 80 ± 2.6 during the post test. For the skills on BSE techniques, the pre test score was 30 ± 9.8 increasing to 90 ± 4.6 at the time of the post test